Development of a Prediction Model for Acute Kidney Injury after Colistin Treatment for Multidrug-resistant Acinetobacter baumanii Ventilator-Associated Pneumonia: A Pilot Study - Seanglaw, Dussadee; Morasert, Thotsaporn (Journal of Health Science and Medical Research, 2023)
Objective: Multidrug-resistant Acinetobacter baumanii (MDR-AB) ventilator-associated pneumonia (VAP) is the major complication following hospital admission in Thailand, increasing morbidity and prolonging hospital stay duration. Treatment of MDR-AB VAP usually requires colistin which has highly nephrotoxic properties. Therefore, we aimed to develop a pilot prediction model for acute kidney injury (AKI) after colistin treatment. Material and Methods: We conducted a retrospective cohort study. All MDR-AB VAP patients who received colistin for at least 72 hours in Suratthani Hospital from January to July 2017 were eligible for inclusion. The primary outcome was the overall presence of AKI on days 3, 5 or 7 after colistin administration. Multivariable logistic regression analysis was used to develop the final prediction model. Results: Of 85 MDR-AB VAP patients, 51 (61%) developed AKI after colistin treatment. Nine factors, female, intensive care unit (ICU) admission, diabetes mellitus, systolic blood pressure (SBP), diastolic blood pressure (DBP), serum sodium, creatinine, blood urea nitrogen (BUN) and glomerular filtration rate were potential predictors of AKI. Multivariable logistic regression with backward stepwise selection revealed the best prediction model had four predictors: female, ICU admission, BUN, and DBP. The area under the receiver operating characteristic curve for the model in predicting AKI among MDR-AB VAP patients was 0.801 (95% confidence interval: 0.703, 0.898). Conclusion: The prediction model containing four predictors, female gender, ICU admission, BUN level, and DBP had fair to good performance in predicting AKI after colistin treatment among MDR-AB VAP patients.